Secular trends of socio-demographic and lifestyle characteristics among delivering women in Arctic Russia, 1973-2017. Issue 1 (31st December 2023) - Treskina, Natalia A.; Postoev, Vitaly A.; Usynina, Anna A.; Grjibovski, Andrej M.; Odland, Jon Øyvind
ABSTRACT: The aim of this study was to describe temporal trends in socio-demographic and lifestyle characteristics among delivering women in two Northern provinces of Russia from 1973 to 2017. Totally 161, 730 births were registered in three birth registries. Changes in the distribution of maternal age, education, marital status, smoking during pregnancy were studied using Pearson's chi-squared tests and one-way ANOVA. The logistic regression models were used to assess factors, contributing to the variations in the prevalence of maternal smoking. The mean age of primiparous mothers increased from 22.1 years in 1973–1980 to 25.4 years in 2012–2017 (p < 0.001). The proportion of primiparous mothers with higher education increased from 26.2% in 2006 to 38.3% in 2017 (p < 0.001). The proportion of cohabiting primiparous women increased from 5.0% to 15.2% over the study period (p < 0.001). The proportion of mothers smoking during pregnancy decreased from 18.9% in 2006–2011 to 14.8% in 2012–2017 (p < 0.001). Downward in the prevalence of smoking was revealed in 2012–2017 compared to 2006–2011 (OR = 137.76; 95%CI:71.62–264.96, OR = 183.74; 95%CI:95.52–353.41, respectively). Over the past decades, women postpone childbearing until receiving higher education, continue living in cohabitation during pregnancy and smoke less.